Can preoperative neopterin levels predict acute kidney injury in patients undergoing on-pump cardiac surgery? - Çiçek Ömer Faruk; Akyürek Fikret; Akbayrak Hakan; Orhan Atilla; Kaya Eyüp Cihan; Büyükateş Mustafa (Türk Biyokimya Dergisi, 2023)
The aim of this study was to investigate the potential of preoperative neopterin levels as a predictive marker for postoperative acute kidney injury (AKI) in patients undergoing on-pump cardiac surgery, in addition to other potential risk factors.